Seed biology and regeneration niche of the threatened cold desert perennial Ivesia webberi A. Gray - Borokini, Israel T.; France, Michael D.; Harmon, Daniel; Shoemaker, Kevin T.; Weisberg, Peter J.; Peacock, Mary M. (Frontiers in Plant Science, 2025)
Understanding the regeneration niche is of critical importance for the conservation of rare plants, yet species-specific information is often lacking for key components of the plant life cycle such as seed dormancy and germination. We conducted a detailed study of the regeneration niche for Ivesia webberi, a U.S. federally threatened forb that is endemic to the Great Basin Desert. Using seeds collected from 11 populations across a span of years, we investigated seed storage behavior, embryo morphology, and interannual and interpopulation seed viability, while testing the efficacy of alternative nondestructive methods to assess seed viability. We also studied the effects of various pre-incubation and incubation treatments on germination rates, speed, and synchrony. An examination of x-ray images showed that I. webberi have non-endospermic seeds with spatulate embryos. We observed a significant reduction in seed viability over three years, suggesting a recalcitrant storage behavior. Seed viability exhibited significant interannual, but not interpopulation, variation across 11 I. webberi populations. Both the x-ray and multispectral imaging are promising nondestructive methods that can replace the widely used, but destructive, tetrazolium test. Across all 68 germination treatments, seed germination was higher, faster, and more synchronized under warmer cold-stratified incubation temperatures. Seed germination was significantly increased by pre-incubation chilling and reduced by pre-incubation heat treatments, while pre-incubation and incubation light exposures had no effect. Both the seed embryo morphology and germination experiments suggest physiological dormancy in I. webberi. Results suggest that warmer and shorter winters, such as are consistent with predicted climate change, could increase germination of I. webberi seeds.